FOXN1 deficient nude severe combined immunodeficiency. Issue 1 (December 2017) - Rota, Ioanna; Dhalla, Fatima
Abstract Nude severe combined immunodeficiency is a rare inherited disease caused by autosomal recessive loss-of-function mutations inFOXN1 . This gene encodes a transcription factor essential for the development of the thymus, the primary lymphoid organ that supports T-cell development and selection. To date nine cases have been reported presenting with the clinical triad of absent thymus resulting in severe T-cell immunodeficiency, congenital alopecia universalis and nail dystrophy. Diagnosis relies on testing forFOXN1 mutations, which allows genetic counselling and guides therapeutic management. Options for treating the underlying immune deficiency include HLA-matched genoidentical haematopoietic cell transplantation containing mature donor T-cells or thymus tissue transplantation. Experience from other severe combined immune deficiency syndromes suggests that early diagnosis, supportive care and definitive management result in better patient outcomes. Without these the prognosis is poor due to early-onset life threatening infections.